An innovative Strategic Spatial Planning Model: The Municipal Unity of Thermi (Thessaloniki-Greece) case study - Lampru, Thanasēs (Cogent social sciences, 2017)
Strategy is distinguished as a widely discussed issue inside the scientific world. Strategic Planning constitutes an appropriate and systematic method of strategy formulation and implementation. Characteristic models of Strategic Planning are initially presented in this paper in order to analyze the characteristics and differentiations in different levels. This paper presents an unconventional Strategic Spatial Planning model in the Municipal Unity of Thermi (Thessaloniki) for the strategic arrangement of the emerging development spatial issues. The main aim of the proposed model is the identification and formulation of Specific Actions Programs which are prioritized through a composite application of integrated multicriteria decision-making methods.